Significações atribuídas ao exercício do cuidado em fim de vida - Espíndola, Amanda Valério (2018)
Global enhancing on life expectation is related to an important epidemiological change. If previously morbidity and mortality were caused by infectious and parasitic diseases, since mid-1900 those rates had started to be led by noncommunicable diseases (NCD). Driven by the improvement on sanitary conditions and scientific progress, health professionals aim to control and to heal chronic illness, which might cause dysthanasia, that is comprehended as the usage of futile interventions in the end of life. On the other hand, palliative care consists on a model of care that aims to promote quality of life to those people who are diagnosed with life-threatening diseases, as well as to their family members, through the reduction of physical, psychosocial and spiritual sufferings. As final outcome, this model of care aims death with dignity – orthothanasia. Facing these aspects, this dissertation aimed to comprehend the meanings attributed to family relationships in the end of life, by the perspective of people who are receiving palliative home care and their family caregivers. It is pointed out that the results of this work were divided in three articles. The first one is a narrative literature review. Yet the second and the third articles consist on empiric studies. In order to perform these last studies, it was used the clinical-qualitative method. Participants were five patients and six family caregivers, who were receiving Home Care Service (HCS) from an university hospital in the state of Rio Grande do Sul, Brazil. For data collection it was used semi-directive interviews, composed by open-ended questions, which were recorded and transcribed. For data analysis, it was used the content analysis. Categories emerged on this process were distributed in two articles entitled “End of life care implications to the family caregiver” and “Family relationships facing the inevitability of death”. Results pointed out to reorganization in family hierarchy in end of life situations, bearing in mind that family caregivers, due to their attributions related to care, are located in relations of dominance in face of other family members. Thus, it is perceived that the care for these people consists on an identity aspect that held a social function. Related to this position of power it is the destitution of autonomy to people facing the end of their lives, which converge to the infantilization of those individuals and to the construction of silence conspiracies towards the end of life.